Cultural competence in higher education - Puckett, Tiffany; Lind, Nancy S. (Innovations in higher education teaching and learning, 2020)
This book covers teaching cultural competence in colleges and universities across the United States, providing a comprehensive reference for instructors, researchers, and other stakeholders who are looking for material that will assist them in working to prepare students to become culturally competent.